SIMULTANEOUS ESTIMATION OF ISONIAZID AND PYRIDOXINE HYDROCHLORIDE IN TABLET DOSAGE FORM BY SPECTROPHOTOMETRY ULTRAVIOLET WITH AREA UNDER CURVE METHOD - Nasution, Lisda Rimayani; Bachri, Muchlisyam; Putra, Effendy De Lux (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study aimed to develop spectrophotometry ultraviolet (UV) method by area under curve (AUC) to determine the levels of isoniazid (INH) and pyridoxine hydrochloride (PDX) in commercial tablets. Methods: Spectrophotometry UV method by AUC tested is carried out by optimizing the type of solvent, methanol, mixture of methanol, and phosphate buffer pH 4, pH 5, and pH 6 at a ratio of 90:10. The AUC value of each spectrum in various concentrations is calculated to selected wavelength range analysis. Then, this method was applied to determine the levels of INH and PDX in commercial tablets. Results: The application of AUC spectrophotometry UV method for determining the levels of INH and PDX was performed on wavelength range 262.2–272.2 nm and 289.8–299.8 nm, respectively. The selection of wavelengths based on wavelengths gives the best result. The mean % recoveries were found to be at 99.69% and 101.09% for INH and PDX, respectively. Conclusion: The method is successfully applied to analyze INH and PDX in pharmaceutical formulation simultaneously with no interference from excipients as indicated by all validation parameters which were within the acceptable range.